Android-based Programming Language to Natural Language Translator App - Rosydah Rihadhatu Aisyiyah; Ade Eviyanti (SAGA: Journal of Technology and Information System, 2025)
Translation between programming languages and natural languages is an important solution to improve the understanding of coding in informatics students who often have difficulty understanding the syntax rules of programming languages. This research develops a translator application that is integrated with OCR technology and uses GPT Chat API to automatically translate text. This application supports seven programming languages (Python, Kotlin, CSS, Dart, HTML, Javascript, and Java) and two natural languages (Indonesian and English). This research uses the Waterfall software development method, starting from requirements analysis, system design, implementation, to testing using the blackbox method. The results show that this application can help users understand coding more effectively and efficiently through translation features, interactive quizzes, and user activity history. Thus, this application has the potential to be an innovative learning media that improves the programming skills of informatics students.